Modelling Gas Transmission in Cylindrical Dynamic Accumulation Oxygen Transmission Rate Chambers to Explore Implications of Oxygen Sensor Location Relative to Samples. (7th February 2014) - Abdellatief, Ayman; Welt, Bruce A.; Butler, Jason; McLamore, Eric; Teixeira, Arthur A.; Shukla, Sanjay
<x xml:space="preserve">Abstract</x> A model was developed to simulate oxygen accumulation in space and time within cylindrical dynamic accumulation chambers that are used to measure oxygen transmission rate (OTR) of materials. The model is based on Fick's law of diffusion and was validated against actual OTR measurements of polymer film samples. Measured OTR values and thicknesses were inputted into the model and oxygen concentrations outputted by the model. OTRs determined from the output of the model was in close agreement to within 0.3–3% of the measured OTR. Oxygen concentration versus time curves generated from model output oxygen concentrations and experimentally measured oxygen concentrations for three actual films were also in agreement. The model was then used to simulate results from three hypothetical test films at varying chamber lengths in order to evaluate effects of accumulation chamber dimensions relative to films on resulting OTR measurements. A typical design scenario was used, where the oxygen sensor is mounted on the chamber wall opposite the sample film. Results demonstrate that dynamic accumulation OTR instrument designers have considerable flexibility in choosing accumulation chamber dimensions because deviations in OTR are only expected to occur at impractically extreme chamber lengths (>10 m) for the entire envelope of OTRs expected for typical packaging films. Copyright © 2014 John Wiley & Sons, Ltd.